Q. 1 O4.0( 10 Votes )

<span lang="EN-US

Answer :

For getting in the equation


(a2 – b2 ) = (a + b)(a-b)


RHS would be


3a2 – 4b2


Then LHS would be


3a2 – 4b2


= (3a – 4b)(3a + 4b)


The error is (a – b) instead of (3a – 4b)


3a2 – 4b2 instead of 3a2 – 4a2


Hence 3a2 – 4b2 = (3a – 4b)(3a + 4b)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics